Ancestral connections and corporate alliances - Pan, Yihui; Peng, Xiaoxia (Journal of Corporate Finance, 2023)
This paper studies how culture works as an implicit incentive alignment mechanism in corporate alliances. We measure the ancestral connection between different corporate headquarters places, using historical immigration from different countries to different areas of the U. S. When forming business alliances, the ancestral composition of the area where firms locate plays an important role in their choices of partners and the location of new ventures. Exploiting immigration to U.S. cities induced by WWI and the immigration acts of the 1920s, we find that ancestral connection driven by the supply-push component of historical immigrant inflows is associated with an increase in alliance intensity today. Finally, partnering firms experience significantly better performance when the ancestral connection between their headquarters or between their inventors is stronger. Shared values and beliefs between firms' key stakeholders likely underlie the role of ancestral connection.